Book Review: Global Climate Justice Theory and Practice - Agudelo-Herrera, Isabella (2023)
The book "Global Climate Justice: Theory and Practice" provides a comprehensive view of climate justice from diverse theoretical approaches by exploring diverse perspectives on the distribution of CO2 and climate responsibility. The text examines controversial viewpoints, such as the right of oil companies to receive compensation for profit losses, as well as historical approaches that consider the persistent effects of colonization on states' capacity to address climate change and the consequent responsibility of colonizing states. The review emphasizes the historical context driving the need to implement environmental justice. Additionally, it highlights the diversity of theoretical perspectives presented in the book and their relevance in formulating international policies.